Developing a Quality-Embedded EVM Tool to Facilitate the Iron Triangle in Architectural, Construction, and Engineering Practices - Ong, Hong Yeow; Wang, Chen; Zainon, Nurshuhada (American Society of Civil Engineers, 2018)
In modern architecture, engineering, and construction (AEC) practices, the Iron Triangle of schedule, cost, and quality remains the key measurement to gauge project success. Existing tools do not work well at monitoring all three measures of the Iron Triangle, resulting in a huge cost and time overrun, and the existing functionality of Earned Value Management (EVM) covers only time and cost, but not quality. Thus, this study aims to develop a quality extension to EVM that caters to quality measurement. Firstly, this research introduced a measurable index and developed a new quality assessment method named the Quality Performed Assessment Method (QPAM) through a quantitative approach. Subsequently, a new tool named Earned Quality Value Management (EQVM) was developed to manage the Iron Triangle in a single reporting setting. The QPAM and EQVM were validated through three tiers of validation processes, namely, a pilot run to test its functionality in a conceptual model, a scenario analysis to identify its sensitivity, and a real case study to validate its functionality. QPAM and EQVM performed satisfactorily in systematic reporting and monitoring enhancement. This single reporting tool enables project stakeholders to make cross-comparisons and gain more insight into the project portfolio. Academically, this research minimized the gap among Iron Triangle management, quality management, and project portfolio management. Practically, this research developed a method for Iron Triangle control on a daily basis for both a single project and a portfolio.